Conceptualizing color-evasiveness: using dis/ability critical race theory to expand a color-blind racial ideology in education and society. Issue 2 (4th March 2017) - Annamma, Subini Ancy; Jackson, Darrell D.; Morrison, Deb
Abstract: Color-blind racial ideology has historically been conceptualized as an ideology wherein race is immaterial. Efforts not to 'see' race insinuate that recognizing race is problematic; therefore, scholars have identified and critiqued color-blindness ideology. In this paper, we first examine Gotanda's (1991) identification and critique of color-blind racial ideology, as it was crucial in troubling white supremacy. We then explore literature in both legal studies and education to determine how scholars have built upon Gotanda's intellectual theoretical foundations. Finally, using a Dis/ability Critical Race Theory (DisCrit) framework, we end by expanding to a racial ideology of color-evasiveness in education and society, as we believe that conceptualizing the refusal to recognize race as 'color-blindness' limits the ways this ideology can be dismantled.